Ergebnisse der Albanien-Expedition 1961 des 'Deutschen Entomologischen Institutes'. 83. Beitrag. Coleoptera: Cantharidae II (Genus Malthodes). - Wittmer, Walter (Contributions to Entomology = Beiträge zur Entomologie, 1971)
In continuation of the 73th contribution to the series of publications on the Cantharidae excluding the Malthinini by C. Moscardini, a revision of the genus Malthodes is presented. The expedition made by DEI had yielded 105 individuals of this genus. Of these, 85 individuals belonged to a new species, which is described as Malthodes carinatopygus. Two femalis can not yet be determined as to their species. The evaluation of the remaining 12 Malthinini collected by this expedition must be postponed until the time after a revision of the genera Malchinus and Malthinus.Nomenclatural Actscarinatopygus Wittmer, 1971 (Malthodes), spec. n.